2014
DOI: 10.1007/s00428-014-1536-3
|View full text |Cite
|
Sign up to set email alerts
|

High GOLPH3 expression is associated with a more aggressive behavior of epithelial ovarian carcinoma

Abstract: Overexpression of GOLPH3 (Golgi phosphoprotein 3, 34 kDa) is associated with the progression of many solid tumor types leading to an unfavorable clinical outcome. The present study examined the association between GOLPH3 expression and tumor development, clinicopathological factors, and prognosis of epithelial ovarian carcinoma. GOLPH3 expression was examined by immunohistochemistry in 18 normal ovarian samples, 28 benign tumors, 55 serous borderline ovarian tumors, and 135 epithelial ovarian carcinomas. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Moreover, DFS of patients with NSCLC and high GOLPH3 overexpression was poorer compared with that of patients with NSCLC and low GOLPH3 expression. Subsequently, we found that GOLPH3 expression in NSCLC was notably Previous studies revealed that GOLPH3 is closely related to the occurrence and development of malignant solid tumours, such as renal, ovarian, breast, and oesophageal cancers [17][18][19][20]. To our knowledge, this study is the first to indicate an association between GOLPH3 positivity in patients with NSCLC and poor prognosis and to suggest that GOLPH3 expression may be an independent prognostic factor for patients with NSCLC.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, DFS of patients with NSCLC and high GOLPH3 overexpression was poorer compared with that of patients with NSCLC and low GOLPH3 expression. Subsequently, we found that GOLPH3 expression in NSCLC was notably Previous studies revealed that GOLPH3 is closely related to the occurrence and development of malignant solid tumours, such as renal, ovarian, breast, and oesophageal cancers [17][18][19][20]. To our knowledge, this study is the first to indicate an association between GOLPH3 positivity in patients with NSCLC and poor prognosis and to suggest that GOLPH3 expression may be an independent prognostic factor for patients with NSCLC.…”
Section: Discussionmentioning
confidence: 69%
“…An increasing number of papers has shown that GOLPH3 drives cancer in several other solid tumors such as Neuroblastoma (NB) [42], Non-Small Cell Lung Cancer (NSLC) [89], epithelial ovarian carcinoma [90], prostate cancer [91,92], gastric cancer [93], and hepatocellular carcinoma [94,95] ( Figure 2). Recent reports indicate that GOLPH3 overexpression can be used as a positive biomarker for tumor progression and poor survival in these cancer types [89][90][91][92][93][94][95][96][97][98]. Experimental data in cancer cell lines or in nude mice revealed the role of GOLPH3 in cell proliferation, metastasis formation and angiogenesis ( Figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…This protein localizes to the cytoplasmic face of the trans-Golgi and has been closely associated with tumorigenicity [3] , [8] . Large studies have found that GOLPH3 overexpression occurs in several human cancers, including epithelial ovarian carcinoma, renal cell carcinoma, glioblastoma multiforme, esophageal squamous cell carcinoma, and oral tongue cancer [12] [16] . Evidence suggests that GOLPH3 is involved in tumorigenesis and correlates with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%